MULTIDIMENSIONAL SCALING: STRATEGI MEMASARKAN DESTINASI PARIWISATA BALI - I Nyoman Sudiarta; I Wayan Suardana; Nyoman Ariana (Institut Pariwisata dan Bisnis Internasional, 2014)
Various strategies used by the company, organization, and a tourism destination to be able to win the competition and retain customer loyalty even increase. This paper aims to develop a research model using one of the multivariate analysis tool that call Multidimensional Scaling (MDS) and Coresponden Analysis (Anacor) so that it can be known the position of 12 tourist attraction in Bali, namely the similarities, differences and preferences of domestic tourists. Twelve of tourist attraction in Bali, Kuta and Sanur is the attractiveness of the most known and desirable while the less popular and less known is Medewi beach. Medewi Beach perceived as a tourist attraction because of its location differs considerably compared with Kuta. Tourist attraction which is also considered to have to be defferent is Tanah Lot and Sanur. While the rest are considered to have equal or proximity including Tanjung Benoa, Tulamben, Kuta, Nusa Dua and Ubud. Tanah Lot and Ubud are considered to have more advantages in terms of art and culture and spiritual destination.